Composite-structure-defined nitrogen-doped carbon nanocage embedded Co/CoxP for enhanced oxygen reduction and evolution reactions. (1st January 2023) - Fan, Fangfang; Huang, Qiulan; Devasenathipathy, Rajkumar; Peng, Xinglan; Yang, Fan; Liu, Xiaotian; Wang, Limin; Chen, Du-Hong; Fan, Youjun; Chen, Wei
Highlights: Component-structure-defined carbon nanocages embedded Co/CoxP (Co/CoxP/HNC) are synthesized The performance-dependence on shell-thickness and doped-P-content are revealed. Co/CoxP/HNC-5 exhibits outstanding electrocatalytic activity for ORR and OER. Zn-air battery based on Co/CoxP/HNC-5 shows excellent charge/discharge stability. Abstract: The design and synthesis of composite-structure-defined bifunctional oxygen reduction and evolution reactions electrocatalysts for rechargeable Zn-air batteries are highly important. Herein, a facile surface functionalization-carbonization-phosphidation strategy is proposed to construct a novel composition-structure-controllable nanomaterial from a zeolite imidazole ester framework (ZIF67), which has been applied in oxygen evolution reaction (OER), oxygen reduction reaction (ORR), and Zn-air batteries. In the typical nanomaterial, Co and Cox P (a mixture of Co2 P and CoP) were embedded in hollow N-doped carbon shell (Co/Cox P/HNC-5). The relationship between the activity and shell thicknesses of the carbonization products of ZIF67 coated with different mass ratios of polydopamine has been studied. In addition, the doped P-content showed a significant impact on the bifunctional oxygen activity, especially for Co/Cox P/HNC-5. Benefiting from the unique structure, multiple compositions, and synergistic effects, the superior bifunctional oxygen electrocatalytic activity (ΔE = 0.667 V) were obtained on Co/Cox P/HNC-5. Furthermore, Co/Cox P/HNC-5 served as an air-cathode catalyst and exhibited remarkable peak power density, specific capacity and durability in a practical Zn-air battery. This work provides a strategy for the construction of efficient bifunctional electrocatalysts with special structure and adjustable compositions. Graphical abstract: Image, graphical abstract